Survival of 352 titanium implants placed in 181 patients: a 4-year multicenter field study - Shin, Seung-Il; Yun, Jeong-Ho; Kim, Sung-Geun; Park, Byoungkyou; Herr, Yeek; Chung, Jong-Hyuk (Journal of periodontal & implant science, 2014)
The aim of this retrospective chart review was to evaluate the four-year survival rate of a titanium implant system. A total of 352 sand-blasted, thermally acid-etched titanium implants were inserted into 181 partially or completely edentulous patients. Their cumulative survival rate was evaluated retrospectively. Associated factors, such as the implant distribution and treatment type were included in the evaluation. The implants were equally distributed between the maxilla (52.3%) and the mandible (47.7%). 48 implants (13.6%) were placed in the anterior region and 304 implants (86.4%) in the posterior region. The majority of the implants were inserted into bone of type II and III quality (89.8%) and volume (quantity B and C, 87.2%). Most of the implants (70.7%) were restored as single crowns; 28.7% supported a bridge construction and 0.6% a full denture. Only one implant failed, resulting in a four-year cumulative survival rate of 99.7%. The implant system showed an excellent four-year survival rate. It proved to be a safe and predictable means for restoration of the dentition in partially or completely edentulous patients.